Global invasion dynamics of the charru mussel Mytella strigata (Hanley, 1843): mechanisms, impacts, knowledge gaps, and biosecurity implications - Paravanparambil Rajakumar Jayachandran; Pei-Zhen Ma; Marcel Velásquez; Broc S. Kokesh; Mantodi Jima; Kaent Immanuel N. Uba; César Lodeiros; Naduvilakkandy Vishnudattan; Luiza Costa Mello; Rafael Metri; Pablo Damian Borges Guilherme; Pablo Muniz; et al. (Hydrobiologia, 2026)

Aqueous acid washing as an effective pretreatment strategy for crude algal oil refining: Enrichment of fatty matter and reduction of impurities - Camille Zhi Qing P'ng; Mun Yuen Chang; Siti Hanifah Adiiba; Sheau Chien Chee; Noorazlenawati Borhan; Mohammad Ghadaffi Mohd Nor; Tg M. Uzaini Tg Mat; Cher Pin Song; Eng-Seng Chan (Algal Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Modelling climatic variable impacts on ground-level ozone in Malaysia using backward trajectory and Generative Additive Models - F. P. Chee; M. C.-G. Ooi; Y. J. Wong; J. Sentian; J. Dayou; M. T. Latif; J. H.-W. Chang (International Journal of Environmental Science and Technology, 2025)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Phenotypic screening in Organ-on-a-Chip systems: a 1537 kinase inhibitor library screen on a 3D angiogenesis assay - Camilla Soragni; Karla Queiroz; Chee Ping Ng; Arthur Stok; Thomas Olivier; Dora Tzagkaraki; Jeroen Heijmans; Johnny Suijker; Sander P. M. de Ruiter; Aleksandra Olczyk; Marleen Bokkers; Frederik Schavemaker; et al. (Angiogenesis, 2024)
Modern drug development increasingly requires comprehensive models that can be utilized in the earliest stages of compound and target discovery. Here we report a phenotypic screening exercise in a high-throughput Organ-on-a-Chip setup. We assessed the inhibitory effect of 1537 protein kinase inhibitors in an angiogenesis assay. Over 4000 micro-vessels were grown under perfusion flow in microfluidic chips, exposed to a cocktail of pro-angiogenic factors and subsequently exposed to the respective kinase inhibitors. Efficacy of compounds was evaluated by reduced angiogenic sprouting, whereas reduced integrity of the main micro-vessel was taken as a measure for toxicity. The screen yielded 53 hits with high anti-angiogenicity and low toxicity, of which 44 were previously unassociated with angiogenic pathways. This study demonstrates that Organ-on-a-Chip models can be screened in high numbers to identify novel compounds and targets. This will ultimately reduce bias in early-stage drug development and increases probability to identify first in class compounds and targets for today’s intractable diseases.

Hydroxychloroquine: Key therapeutic advances and emerging nanotechnological landscape for cancer mitigation - Liang Ee Low; Chee Kei Kong; Wei-Hsum Yap; Sangeetaprivya P. Siva; Siew Hua Gan; Wei Sheng Siew; Long Chiau Ming; Ashley Sean Lai-Foenander; Sui Kiat Chang; Wai-Leng Lee; Yongjiang Wu; Kooi-Yeong Khaw; et al. (Chemico-Biological Interactions, 2023)

Environment and shipping drive environmental DNA beta‐diversity among commercial ports - Jose Andrés; Paul Czechowski; Erin Grey; Mandana Saebi; Kara Andres; Christopher Brown; Nitesh Chawla; James J. Corbett; Rein Brys; Phillip Cassey; Nancy Correa; Marty R. Deveney; et al. (Molecular Ecology, 2023)
The spread of nonindigenous species by shipping is a large and growing global problem that harms coastal ecosystems and economies and may blur coastal biogeographical patterns. This study coupled eukaryotic environmental DNA (eDNA) metabarcoding with dissimilarity regression to test the hypothesis that ship‐borne species spread homogenizes port communities. We first collected and metabarcoded water samples from ports in Europe, Asia, Australia and the Americas. We then calculated community dissimilarities between port pairs and tested for effects of environmental dissimilarity, biogeographical region and four alternative measures of ship‐borne species transport risk. We predicted that higher shipping between ports would decrease community dissimilarity, that the effect of shipping would be small compared to that of environment dissimilarity and shared biogeography, and that more complex shipping risk metrics (which account for ballast water and stepping‐stone spread) would perform better. Consistent with our hypotheses, community dissimilarities increased significantly with environmental dissimilarity and, to a lesser extent, decreased with ship‐borne species transport risks, particularly if the ports had similar environments and stepping‐stone risks were considered. Unexpectedly, we found no clear effect of shared biogeography, and that risk metrics incorporating estimates of ballast discharge did not offer more explanatory power than simpler traffic‐based risks. Overall, we found that shipping homogenizes eukaryotic communities between ports in predictable ways, which could inform improvements in invasive species policy and management. We demonstrated the usefulness of eDNA metabarcoding and dissimilarity regression for disentangling the drivers of large‐scale biodiversity patterns. We conclude by outlining logistical considerations and recommendations for future studies using this approach.

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of MitraClip Therapy on Mitral Flow Patterns and Vortex Formation: An In Vitro Study - Shelley Chee-Mei Gooden; Hoda Hatoum; Konstantinos Dean Boudoulas; Mani A. Vannan; Lakshmi P. Dasi (Annals of Biomedical Engineering, 2022)

Bird diversity on shelf islands does not benefit from recent land‐bridge connections - Yong Chee Keita Sin; Nadiah P. Kristensen; Chyi Yin Gwee; Ryan A. Chisholm; Frank E. Rheindt (Journal of Biogeography, 2022)
Aim Research in island biogeography has long focused mainly on present‐day island configurations. Recently, there has been an increasing focus on islands’ past histories of land connection, shape and size. Moreover, continental islands (=shelf islands) have received less attention than oceanic islands, and species inventories from extremely small islands are lacking in many datasets. We examine the effects of sea‐level rise since the Last Glacial Maximum (LGM) on bird species diversity and composition of tropical shelf islands in Southeast Asia. Location Sundaland. Taxon Birds. Methods We compiled avifaunal island inventories for 94 islands using an exhaustive literature review of historic surveys of larger islands combined with our own comprehensive island surveys from both small and large islands. Using generalised least‐squares models with spatial autocorrelation, we assessed the importance of traditional biogeographical parameters including area, maximum elevation, distance from mainland and geographical isolation, along with post‐LGM effects of change in island area and duration since isolation. We also compared the species composition on similar‐sized shelf islands from two categories—recently submerged and unsubmerged—using non‐metric multidimensional scaling. Results Post‐LGM effects on species diversity are minimal and insular diversity is instead well explained by present‐day island characteristics, such as area, distance to mainland and proportion of land surrounding an island within a 10 km radius (Cox and Snell Pseudo‐ R 2 = 0.803). Avifaunal diversity is similar across recently submerged and unsubmerged small shelf islands. Main conclusion Avifaunal diversity on tropical shelf islands equilibrates rapidly after isolation, indicating that both extinction and immigration rates are high. In particular, a high immigration rate of dispersive species maintains diversity, especially on small islands. Over‐water dispersal is generally restricted to short distances among Sundaic birds. Consequently, the diversity of an island can be maintained by the presence of large or stepping‐stone islands near it.

Microbiome and environment explain the absence of correlations between consumers and their diet in Bornean microsnails - Kasper P. Hendriks; Karen Bisschop; Hylke H. Kortenbosch; James C. Kavanagh; Anaïs E. A. Larue; Phung Chee‐Chean; Dries Bonte; Elza J. Duijm; Joana Falcão Salles; Alex L. Pigot; Francisco J. Richter Mendoza; Menno Schilthuizen; et al. (Ecology, 2021)
Classical ecological theory posits that species partition resources such that each species occupies a unique resource niche. In general, the availability of more resources allows more species to co‐occur. Thus, a strong relationship between communities of consumers and their resources is expected. However, correlations may be influenced by other layers in the food web, or by the environment. Here we show, by studying the relationship between communities of consumers (land snails) and individual diets (from seed plants), that there is in fact no direct, or at most a weak but negative, relationship. However, we found that the diversity of the individual microbiome positively correlates with both consumer community diversity and individual diet diversity in three target species. Moreover, these correlations were affected by various environmental variables, such as anthropogenic activity, habitat island size, and a possibly important nutrient source, guano runoff from nearby caves. Our results suggest that the microbiome and the environment explain the absence of correlations between diet and consumer community diversity. Hence, we advocate that microbiome inventories are routinely added to any community dietary analysis, which our study shows can be done with relatively little extra effort. Our approach presents the tools to quickly obtain an overview of the relationships between consumers and their resources. We anticipate our approach to be useful for ecologists and environmentalists studying different communities in a local food web.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Simulation analysis of the future surface ozone in Malaysian region under representative concentration pathways (RCPs) emission scenarios - S. S. K. Kong; J. Sentian; M. T. Chuang; M. C. G. Ooi; F. P. Chee; J. H. W. Chang (International Journal of Environmental Science and Technology, 2019)

Infection criteria, inoculum sources and splash dispersal pattern of Colletotrichum acutatum causing bitter rot of apple in New Zealand - K. R. Everett; I. P. S. Pushparajah; O. E. Timudo; A. Ah Chee; R. W. A. Scheper; P. W. Shaw; T. M. Spiers; J. T. Taylor; D. R. Wallis; P. N. Wood (European Journal of Plant Pathology, 2018)

Phytochemicals in Ischemic Stroke - Joonki Kim; David Yang-Wei Fann; Raymond Chee Seong Seet; Dong-Gyu Jo; Mark P. Mattson; Thiruma V. Arumugam (NeuroMolecular Medicine, 2016)

Isolation and Characterization of Circadian Clock Genes in the Biofuel Plant Pongamia (Millettia pinnata) - Harry P. Winarto; Lim Chee Liew; Peter M. Gresshoff; Paul T. Scott; Mohan B. Singh; Prem L. Bhalla (BioEnergy Research, 2015)

The pathology of ‘scale drop syndrome’ in Asian seabass, Lates calcarifer Bloch, a first description - S Gibson‐Kueh; D Chee; J Chen; Y H Wang; S Tay; L N Leong; M L Ng; J B Jones; P K Nicholls; H W Ferguson (Journal of Fish Diseases, 2012)
This is the first pathological description of ‘scale drop syndrome’ (SDS) in Asian seabass, Lates calcarifer Bloch. Cumulative mortality was estimated at 40–50%. The vasculitis in all major organs including the skin and associated tissue necrosis was distinctive. The dermis overlying scale beds was often necrotic and associated with scale loss. Necrosis of splenic ellipsoids, renal glomeruli and choroid rete glands of eye were further hallmarks of a disease with systemic vascular involvement. The brain was not spared vascular damage, and the resulting multifocal encephalomalacia probably accounts for the spiral swimming behaviour in some affected fish. Other lesions included accentuated hepatic lobulation and gastric gland necrosis. Nuclear chromatin margination and karyolysis in hepatocytes, renal tubular epithelium and gastric and intestinal epithelium suggest specific targeting of cells. Basophilic cytoplasmic inclusions were present in spleen, kidney, liver, heart and choroid rete, but they were not prominent. Using transmission electron microscopy, two morphological forms of virions were observed: single‐ and double‐enveloped hexagonal virions. Based on size and morphology, these virions resemble iridovirus or herpesvirus. The cause of SDS is unknown, but the pathological changes, especially the vasculitis, suggest an infectious aetiology, possibly viral.

Status of the USA cotton germplasm collection and crop vulnerability - T. P. Wallace; D. Bowman; B. T. Campbell; P. Chee; O. A. Gutierrez; R. J. Kohel; J. McCarty; G. Myers; R. Percy; F. Robinson; W. Smith; D. M. Stelly; et al. (Genetic Resources and Crop Evolution, 2009)

Resistance exercise effects on blood glutathione status and plasma protein carbonyls: influence of partial vascular occlusion - A. H. Goldfarb; R. S. Garten; P. D. M. Chee; C. Cho; G. V. Reeves; D. B. Hollander; C. Thomas; K. S. Aboudehen; M. Francois; R. R. Kraemer (European Journal of Applied Physiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Rhizosphere bacteria enhance the accumulation of selenium and mercury in wetland plants - M. P. de Souza; C. P. A. Huang; N. Chee; N. Terry (Planta, 1999)

Isolation and characterization of the zSSIIa and zSSIIb starch synthase cDNA clones from maize endosperm - Chee Harn; Mary Knight; Aravind Ramakrishnan; Hanping Guan; Peter L. Keeling; Bruce P. Wasserman (Plant Molecular Biology, 1998)

Microbial reductive dechlorination of PCBs - James M. Tiedje; John F. Quensen; Joann Chee-Sanford; Joshua P. Schimel; Stephen A. Boyd (Biodegradation, 1993)